2019
DOI: 10.1186/s12866-019-1481-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a bacteriophage with broad host range against strains of Pseudomonas aeruginosa isolated from domestic animals

Abstract: Background Pseudomonas aeruginosa is an opportunistic pathogen and one of the leading causes of nosocomial infections. Moreover, the species can cause severe infections in cystic fibrosis patients, in burnt victims and cause disease in domestic animals. The control of these infections is often difficult due to its vast repertoire of mechanisms for antibiotic resistance. Phage therapy investigation with P. aeruginosa bacteriophages has aimed mainly the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
32
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 86 publications
4
32
1
Order By: Relevance
“…Their genomes are typically organized in clusters. Both guanine-cytosine content and genome length were similar to other Pbunaviruses as previously reported ( de Melo et al, 2019 ; Yuan et al, 2019 ). Regarding vB_PaeM_USP_18 and vB_PaeM_USP_25, only ca.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Their genomes are typically organized in clusters. Both guanine-cytosine content and genome length were similar to other Pbunaviruses as previously reported ( de Melo et al, 2019 ; Yuan et al, 2019 ). Regarding vB_PaeM_USP_18 and vB_PaeM_USP_25, only ca.…”
Section: Discussionsupporting
confidence: 86%
“…Infection of multidrug-resistant P. aeruginosa indicates that bacteriophages or bacteriophage-based products could potentially be applied for therapeutic purposes. The lytic rates presented here are higher than in other Pbunavirus ( de Melo et al, 2019 ), which can be related to the origin and the number of tested strains. In fact, host broad range and species specificity are desirable for bacteriophage application in phage therapy.…”
Section: Discussioncontrasting
confidence: 50%
“…Pbunavirus BrSP1, which is closely related to the Pseudomonas phage NH_4, has a broad host range against domestic animal-related P. aeruginosa strains. 17 It has been suggested that BrSP1 could be useful in a phage cocktail. Our data also indicate that NH_4-like ØS50 would be useful for phage therapy in the field of veterinary medicines.…”
mentioning
confidence: 99%
“…Background 3 P. aeruginosa is an opportunistic pathogen causing infections especially in immunocompromised patients. It is the leading cause of nosocomial infections such as urinary tract infections, surgical site infections, pneumonia, bacteremia and septicaemia [1][2][3] It is one of the ESKAPE pathogens that is most medically and epidemiologically significant and has been implicated as a principal cause of chronic lung infections in cystic fibrosis (CF) patients and severe infections in burn victims [4][5][6][7]. The World Health Organization (WHO) has categorized P. aeruginosa as a critical priority pathogen which needs urgent novel antibiotics intervention and has been given a serious threat level due to multidrug resistance displayed to many antibiotics [8,9].…”
mentioning
confidence: 99%